Research and application of SRv6 Policy for financial backbone network - Lijun ZU; Hang YUAN (Dianxin kexue)
The financial backbone network is an important part of the basic network platform of financial institutions.Under the current background of the country’s promotion of data center cloudification and IPv6,the technical architecture of the financial backbone network must also be optimized and evolved.Based on this research,the application of SRv6 Policy in the financial backbone network was explored.Firstly,the existing problems of traditional solutions based on the current situation of the financial backbone network were analyzed; then the technical advantages and implementation principles of SRv6 Policy were explained.Finally,the application and deployment of SRv6 Policy in the financial backbone network was studied and explored,combined with the management strategy of financial institutions on the business traffic in the backbone network,and optional intelligent tuning solutions were provided for congestion avoidance and path planning scenarios,which further enhanced the stability of the financial backbone network and the ability to guaranteed traffic transmission,and the application feasibility of SRv6 Policy in the financial backbone network was initially verified.